ANALISIS TERHADAP KEKUATAN BARGAINING POSITION PEMERINTAH INDONESIA DALAM KONTRAK KARYA P.T. FREEPORT INDONESIA - Ali Imron (University of Merdeka Malang, 2013)
Along with the increase of good conviction of objective standard in doing agreement, if hardship happenedbecause of condition change, a contract had to be considered or observed again. The spirit of law no 4 year 2009was to return the authority of mineral and coal management under state domain. However, the principle ofSunt Servanda mine contract pact which had existed before should still have been respected, as long as it wasapplicable. Based on constitution, the Republic of Indonesia government must not have placed themselves inthe same level with a business entity in mining contract. A mandate which had to be done by government wasthat natural resource must have been used optimally for people prosperity. Freeport arrival in Papua sincebeginning was with the purpose or goal of business political expansion which was not fair. It came intoIndonesia with the facility from President Soeharto who was famous as the corruption and repressive government.In democratization and transparency era, work contract which was full of manipulation and which wasnot oriented on people prosperity, the existence was actually not proper to be defended. Thus, if now whathappened was only demand to negotiate the unreasonable working contract, it was a very natural or properthing. It also happened to international trade contract practice. After contract was dealt then the fact changedfundamentally, based on article 6.2.2 UPICCs, the result or consequence could be issued to reconsider therunning contract. The purpose of Reconsidering the content of working contract was to return the disturbedbalance. The problem of Freeport work contract was not only law and justice, but there was an interventioneffect of foreign strength and the interest conflict in Indonesian government administration itself. Thus, one ofimportant points which had to be done to improve the contract was by placing an agent of Indonesian governmentin Freeport management until the end of contract, exactly the agent was put in directors board to watchand monitor so there was no divergence anymore.